Public Diplomacy Activities of Korean Cultural Center in Contemporary Theory Perspective - Ji Tae Chung; Faruk Faruk; Oki Rahadianto Sutopo (k@ta: A Biannual Publication on the Study of Languange and Literature, 2023)
This paper focuses on activities of Korean Cultural Center Indonesia (KCCI) through the analysis of Korean government policies regarding public diplomacy by Ministry of Foreign Affairs (MOFA). KCC is affiliated organization under the Korean Culture and Information Service (KOCIS) under Ministry of Culture, Sports and Tourism (MCST). KCC is established in foreign countries to spread Korean culture and enhance national image through political communication with public. Since the beginning, KCCI has shown contradictory tendencies. On one hand, their mission is to show Korea's strength, but on the other hand, they organize cultural exchange programs that imply equality between the Korean side and its partners. By using a public diplomacy 3.0 theory which is based on cosmopolitanism to evaluate KCCI’s practices, this paper finds that practice of public diplomacy by KCCI is still consisted within public diplomacy 2.0 which is focus on enhancement of national image and creation of a favorable diplomatic environment due to holding hegemony in global soft power competition.